Dynamic remodelling of the human host cell proteome and phosphoproteome upon enterovirus infection - Piero Giansanti (Nature Portfolio, 2020)
Here, Giansanti et al. perform a system-wide and time-resolved characterization of the changes in the host cell proteome and phosphoproteome of cells infected with the enterovirus coxsackievirus B3 during a full round of replication and identify mTORC1 signalling as a major regulation network during virus infection.